Lack of truncated IFITM3 transcripts in cells homozygous for the rs12252-C variant that is associated with severe influenza infection - Makvandi-Nejad, S; Laurenson-Schafer, H; Wang, L; Wellington, D; Zhao, Y; Jin, B; Qin, L; Kite, K; Moghadam, H; Song, C; Clark, K; Hublitz, P; et al. (Oxford University Press, 2017)
Interferon-induced transmembrane 3 (IFITM3) is known to restrict the entry of a range of enveloped viruses. The single nucleotide polymorphism rs12252-C within IFITM3 has been shown to be associated with severe influenza A virus infection. It has been suggested that rs12252-C results in expression of a truncated IFITM3 protein lacking the first 21 amino acids. By performing high-throughput RNA sequencing on primary dendritic cells and peripheral blood mononuclear cells isolated from pandemic H1N1 influenza and human immunodeficiency virus-1 (HIV-1) infected patients we show that full-length IFITM3 mRNA is dominantly expressed (>99%) across all rs12252 genotypes. Full-length IFITM3 protein can be detected in all genotypes.